Local sustainability indicators in Portugal: Assessing implementation and use in governance contexts - Moreno Pires, S.
This paper assesses the implementation and use of sustainability indicators (SI) in local governance contexts in Portugal. The need to analyse the development of local SI is considered critical, given the lack of research on the understanding of how, when and by whom SI are implemented and used, particularly in the Portuguese local governance context. The first aim of this article is to map experiences of SI in Portugal by assessing how many local councils developed indicator systems and when, and the major driving-forces and general features of those systems. The second aim is to analyse and compare 7 case studies, in further detail, to explore the governance factors that influence indicator success and how indicators are used within local contexts. Two particular conceptual frameworks were applied to structure research and analysis. Based on a national survey and case study methodology, findings reveal that local SI in Portugal are still in early stages of development. Where SI have been designed earlier, there has been a lack of political commitment and vision, and a need to overcome local government malfunctioning more than the complex obstacles of sustainable development governance. Applying both conceptual frameworks enabled to present critical lessons on the relationship among governance factors and types of uses when implementing SI in Portugal and to suggest the value of this integrated analysis for other governance contexts.